Chemically induced common bean (Phaseolus vulgaris L.) sprouts ameliorate dyslipidemia by lipid intestinal absorption inhibition - Mendoza-Sanchez, Magdalena (2019)
Common beans (Phaseolus vulgaris L.) are recommended as hypolipidemic adjuvants due to their high content of phytochemicals, which can be enhanced by germination and elicitation. The aim of this study was to evaluate the hypolipidemic effect of non-elicited [control (CS)] and chemically elicited [30 mM H2O2, 7 μM chitosan (CH), and 1 and 2 mM salicylic acid (SA)] bean sprouts. Rats were fed with a high fat and fructose diet (HFF) and supplemented with bean sprouts (10%) for twelve weeks. Control- and elicited-common bean sprouts significantly (p < 0.05) decreased serum triacylglycerides (TAG). Sprouts elicited with 1 and 2 mM SA increased fecal TAG excretion, which was related to the inhibition of pancreatic lipase enzyme activity. Hesperidin and soysaponin-I were identified as the main hypotriglyceridemic phytochemicals of bean sprouts according to the chemometric and in silico analyses. Therefore, the hypotriglyceridemic effect of SA-elicited bean sprouts was associated with decreased TAG intestinal absorption